The ABCs of NDCs - Holzmann, Robert (World Bank, Washington, DC, 2019)
Nonfinancial defined contribution (NDC) pension schemes have been successfully implemented since the mid-1990s in a number of European countries. The NDC approach features the lifelong contribution–benefit link of a financial defined contribution scheme, but is based on the pay-as-you-go format. An NDC approach implemented by the rulebook can manage the economic and demographic risks inherent to a pension scheme and by design creates financial sustainability. This paper offers a nontechnical introduction to NDC schemes, their basic elements and advantages over nonfinancial defined benefit schemes, the key technical frontiers of the approach, and the experiences of countries with NDC schemes.